Exploring key issues in early childhood and technology : evolving perspectives and innovative approaches - Donohue, Chip (New York : Routledge, Taylor & Francis Group, 2020)
"Exploring Key Issues in Early Childhood and Technology offers early childhood allies, both in the classroom and out, a cutting-edge overview of the most important topics related to technology and media use in the early years. In this powerful resource, international experts share their wealth of experience and unpack complex issues into a collection of accessibly written essays. This text is specifically geared towards practitioners looking for actionable information on screen time, cybersafety, makerspaces, coding, computational thinking, STEM, AI, and other core issues related to technology and young children in educational settings. Influential thought leaders draw on their own experiences and perspectives, addressing the big ideas, opportunities and challenges around the use of technology and digital media in early childhood. Each chapter provides applications and inspiration, concluding with essential lessons learned, actionable next steps and a helpful list of recommended further reading and resources. This book is a must-read for anyone looking to explore what we know--and what we still need to know--about the intersection between young children, technology, and media in the digital age"--
Foreword / by Milton Chen -- Media and marriage : "From this day forward, for better or for worse" / Lewis Bernstein -- Five things that haven't changed (much) / David Kleeman -- Fred Rogers : the media mentor we need to navigate the digital age / Chip Donohue -- Smart phones and tablets and kids, oh my, oh my / Ellen Wartella -- When the technology disappears / Lydia Plowman -- Seeing is believing : racial diversity in children's media / Kevin A. Clark -- Claiming rights and righting wrongs : children's rights in the digital environment / Sonia Livingstone -- Child-centered design : integrating children's rights and ethics into the heart of the design process / Shuli Gilutz -- Digital play / Susan Edwards -- Coding as another language : why computer science in early childhood should not be STEM / Marina Umaschi Bers -- Personalized education and technology : how can we find an optimal balance? / Natalia Kucirkova -- Makerspaces in the early years : enhancing digital literacy and creativity / Jackie Marsh -- Mobile media and parent-child interaction / Jenny Radesky -- No surprise : families matter in digital-based learning / M. Elena Lopez -- A mission for media mentors : creating critical thinkers / Lisa Guernsey -- Digesting the iScreen decade : what should media makers, policymakers and philanthropy do next? / Michael H. Levine -- Childhood 2040--a wishlist / Warren Buckleitner -- Afterword: PastForward : why we need thought leaders and media mentors / Chip Donohue.
Includes bibliographical references and index.
Keywords: Early childhood education -- Computer-assisted instruction; Educational technology; Computers and children